The Influence Of Content Marketing And Viral Marketing On Purchase Decisions At Norma Coffee On The Millennial Generation In Pekanbaru - Diamanda, Asyiffa; Rachmad, Ferizal (Basecamp Economics PubMed, 2024)
Norma Coffee is a coffee shop in Pekanbaru that focuses on creating a comfortable atmosphere for various activities, offering high-quality products, and prioritizing consistent, warm, and friendly service. The purpose of this study is to determine the influence of Content Marketing and Viral Marketing on TikTok on Purchase Decisions at Norma Coffee among the Millennial Generation in Pekanbaru. The sample size in this study is 96 respondents, selected using purposive sampling. Data collection was conducted by distributing questionnaires to the respondents. Both primary and secondary data were used. The data analysis method applied is multiple linear regression using SPSS 29 software. The results of partial testing show that the Content Marketing and Viral Marketing variables each have a partial influence on Purchase Decisions. Simultaneous testing results indicate that Content Marketing and Viral Marketing on TikTok have a positive and significant impact on Purchase Decisions at Norma Coffee among the Millennial Generation in Pekanbaru. The R Square value of 0.491, or 49.1%, indicates that Content Marketing and Viral Marketing collectively account for 49.1% of the influence on the Purchase Decision variable, while the remaining 50.9% is influenced by other variables not examined in this study.